2021
DOI: 10.22141/2224-0586.17.4.2021.237723
|View full text |Cite
|
Sign up to set email alerts
|

Main causes of complicated COVID-19 in patients with diabetes mellitus

Abstract: Background. Since December 2019, the new coronavirus disease 2019 (COVID-19) has been marching confidently and aggressively across the planet. On March 11, 2020, the World Health Organization has declared COVID-19 a pandemic. Among the risk factors for the development and severe course of COVID-19, there are old age, arterial hypertension, diabetes mellitus, chronic obstructive pulmonary disease, cardiovascular and cerebrovascular diseases. However, recently, based on the epidemiological data obtained, diabete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 62 publications
(53 reference statements)
0
3
0
2
Order By: Relevance
“…Актуальність дослідження зумовлена тенденцією до зростання поширеності цукрового діабету (ЦД) та тиреоїдної патології, їх коморбідності, особливо в період пандемії коронавірусної інфекції COVID-19. За даними наукових досліджень у 11-23% хворих на ЦД діагностують порушення тиреоїдного гомеостазу (від мінімальної тиреоїдної недостатності до маніфестного гіпотиреозу), а у 13-19% пацієнтів із гіпотиреозом -інсулінорезистентність (ІР), предіабет чи діабет [1][2][3][4][5]. Відомо, що за умов ЦД формується дисфункція гіпоталамо-гіпофізарно-тиреоїдної осі, зменшується секреція тиреотропного гормону (ТТГ) у відповідь на стимуляцію аденогіпофіза тиреоліберином гіпоталамуса.…”
Section: вступunclassified
See 1 more Smart Citation
“…Актуальність дослідження зумовлена тенденцією до зростання поширеності цукрового діабету (ЦД) та тиреоїдної патології, їх коморбідності, особливо в період пандемії коронавірусної інфекції COVID-19. За даними наукових досліджень у 11-23% хворих на ЦД діагностують порушення тиреоїдного гомеостазу (від мінімальної тиреоїдної недостатності до маніфестного гіпотиреозу), а у 13-19% пацієнтів із гіпотиреозом -інсулінорезистентність (ІР), предіабет чи діабет [1][2][3][4][5]. Відомо, що за умов ЦД формується дисфункція гіпоталамо-гіпофізарно-тиреоїдної осі, зменшується секреція тиреотропного гормону (ТТГ) у відповідь на стимуляцію аденогіпофіза тиреоліберином гіпоталамуса.…”
Section: вступunclassified
“…До факторів, які асоційовані з дисфункцією печінки при COVID-19, належать чоловіча стать, похилий вік, надлишкова маса тіла, захворювання самого органа, коморбідна патологія (ендокринні, серцево-судинні захворювання, імунодефіцитні стани та ін.) [1,[10][11][12][13][14][15]. Зазначені зміни вуглеводного, тиреоїдного гомеостазу, гепатобіліарної системи можуть потенціюватися на тлі стресу, що підвищує ризики розвитку захворювань у період війни.…”
Section: вступunclassified
“…Diabetes mellitus is a common complication associated with disorders of glucose and insulin metabolism ( 1 ). Diabetes mellitus is a series of metabolic disorders characterized by hyperglycemia ( 2 ). As a very common chronic disease, diabetes is of increasing concern to patients and physicians worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Results and conclusions: (1) LASSO (Least absolute shrinkage and selection operator) regression analysis yielded a more significant significance on risk factors for progression to diabetic foot in elderly diabetic patients, such as age, presence of peripheral neuropathy, history of smoking, duration of disease, serum lactate dehydrogenase, and high-density cholesterol; (2) Based on the influencing factors and existing theories, a column line graph prediction model for progression to diabetic foot in elderly diabetic patients was constructed. The working characteristic curves of subjects in the training group and their area under the curve (area under the curve = 0.840) were also analyzed simultaneously with the working characteristic curves of subjects in the external validation population and their area under the curve (area under the curve = 0.934), which finally showed that the model was effective in predicting column line graphs; (iii) the C-index in the modeled cohort was 0.840 (95%CI: 0.779-0.901) and the C-index in the validation cohort was 0.934 (95%CI: 0.887-0.981), indicating that the model had good predictive accuracy; the calibration curve fit was good; (iv) the results of the decision curve analysis showed that the model would have good results in clinical use; (v) it indicated that the established predictive model for predicting progression to diabetic foot in elderly diabetic patients had good test efficacy and helped clinically screen the possibility of progression to diabetic foot in elderly diabetic patients and give personalized interventions to different patients in time.…”
mentioning
confidence: 98%
“…[ 1 ] Diabetes mellitus is a spectrum of metabolic disorders characterized by hyperglycemia. [ 2 ] Currently, there are 382 million people living with diabetes mellitus, and the total number is increasing in the world. [ 3 ] Diabetes mellitus is associated with aging-related cardiovascular diseases and kidney diseases due to high glucose levels.…”
Section: Introductionmentioning
confidence: 99%